Physiological Demands of Hurdle Events: Adaptations in Endurance, Strength, and Flexibility - Ramadhan, Muhammad Naufal; Attadillah, Adjie Siddik; Akbar, M. Ghozali Aufathul; Ginting, M. Zaka Gamara (Pusat Pengembangan Olahraga Universitas Pahlawan, 2025)
Introduction: Hurdle events represent a complex athletic discipline requiring the integration of speed, power, technical skill, and specific physiological adaptations. Despite extensive research on sprint events, limited studies have comprehensively examined the multifaceted physiological demands specific to hurdle competitions. Purpose of the Study: This study aimed to investigate the physiological adaptations in endurance, strength, and flexibility among hurdle athletes and determine the correlations between these parameters and competitive performance. Materials and Methods: Twenty-four hurdle athletes (age: 17.2 ± 1.1 years) from SMA Negeri 2 Medan, Sumatera Utara, participated in this correlational study. Participants underwent comprehensive physiological assessments including VO₂max testing, isokinetic strength measurements, and flexibility evaluations. Performance data were collected from official competition records over a 12-month period. Results: Significant correlations were found between hurdle performance times and maximal oxygen uptake (r = -0.68, p < 0.01), lower limb power output (r = -0.74, p < 0.001), and hip flexibility measures (r = -0.56, p < 0.05). Athletes demonstrated superior anaerobic power (738.4 ± 67.2 W) and enhanced range of motion in hip flexion (118.7 ± 8.4°) compared to age-matched controls. Conclusions: Hurdle events demand specific physiological adaptations encompassing aerobic capacity, explosive power, and enhanced flexibility. These findings provide evidence-based guidelines for targeted training interventions in hurdle athletes.